2023
DOI: 10.1002/jcla.24880
|View full text |Cite
|
Sign up to set email alerts
|

Proxalutamide for the treatment of COVID‐19 rebound following Paxlovid treatment: Report of four cases and review of the literature

Abstract: Background: The pandemic the coronavirus disease 2019 (COVID-19) has created a global health crisis. Although Paxlovid is recommended for the early-stage treatment of mild-to-moderate COVID-19 in patients at increased risk of progression to severe COVID-19, more and more cases are reported a COVID-19 rebound after Paxlovid treatment. Currently, information on the additional treatment for COVID-19 rebound following Paxlovid treatment is limited.Case Report: Here, we present four cases with COVID-19 who were mil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Molnupiravir is a prodrug metabolized into an active form, acting as a mutagenic ribonucleoside analog, and inducing mutations in the viral RNA during replication, which can cause errors and prevent the virus from replicating correctly [32]. Other molecules, such as Nirmatrelvir or Bofutrelvir (Figure 1), operate by blocking the main protease (M pro ) of SARS-CoV-2, which is responsible for cutting viral polyproteins into their final functional forms [33,34]. Neither drug is a panacea, as molnupiravir may cause mutations in human DNA, leading regulatory bodies to discourage its use during pregnancy [31].…”
Section: Introductionmentioning
confidence: 99%
“…Molnupiravir is a prodrug metabolized into an active form, acting as a mutagenic ribonucleoside analog, and inducing mutations in the viral RNA during replication, which can cause errors and prevent the virus from replicating correctly [32]. Other molecules, such as Nirmatrelvir or Bofutrelvir (Figure 1), operate by blocking the main protease (M pro ) of SARS-CoV-2, which is responsible for cutting viral polyproteins into their final functional forms [33,34]. Neither drug is a panacea, as molnupiravir may cause mutations in human DNA, leading regulatory bodies to discourage its use during pregnancy [31].…”
Section: Introductionmentioning
confidence: 99%
“…Nirmatrelvir (commercialized as Paxlovid, a combination with another HIV protease inhibitor ritonavir), a SARS-CoV-2 main protease (Mpro) inhibitor developed by Pfizer, was approved for treatment of COVID-19. Although it lowers the risk of hospitalization or death by 89% in individuals with mild to moderate COVID-19 and is effective against Omicron, more and more reports suggested that patients experienced a rebound of COVID-19 symptoms after treatment with Paxlovid and progressed to severe COVID-19 . There is currently limited information available on additional treatments for COVID-19 rebound following Paxlovid treatment.…”
mentioning
confidence: 99%
“…Although it lowers the risk of hospitalization or death by 89% in individuals with mild to moderate COVID-19 and is effective against Omicron, more and more reports suggested that patients experienced a rebound of COVID-19 symptoms after treatment with Paxlovid and progressed to severe COVID-19. 6 There is currently limited information available on additional treatments for COVID- 19 targeted molecules to fight off infections has a long history that dates back over a century (Figure 1). Due to their great specificity and adaptability, monoclonal antibodies (mAbs) are unquestionably in the vanguard of the fight against COVID-19, even though therapeutic mAbs have been widely used to treat a variety of illnesses, including viral infections, and in molecular imaging, drug discovery, and therapeutics for a variety of diseases, including autoimmune, cardiovascular, and infectious diseases, cancer, as well as inflammation (summarized in Figure 2).…”
mentioning
confidence: 99%